Maternal periconceptional environmental exposure and offspring with congenital heart disease: a case-control study in Guangzhou, China - Di Xiao; Weidong Li; Wei-Hong Zhang; Zihao Wen; Weijian Mo; Ciyong Lu; Lan Guo; Li Yang (BMC, 2023)
Abstract Background Congenital heart defects (CHDs) are a major global health problem, yet their crucial environmental risk factors are still unclear. We aimed to explore the associations between maternal periconceptional environmental exposures and all CHDs, isolated and multiple CHDs and CHDs subtypes. Method A case-control study including 675 infants with CHDs and 1545 healthy controls was conducted. Participating mothers who delivered in Guangzhou from October 2019 to November 2021 were recruited. To examine the independent associations between maternal periconceptional environmental exposure and offspring with CHDs, we calculated odds ratios (ORs) and 95% confidence intervals (CIs) using multivariable logistic regression model. Results Maternal exposure to living near main roads [adjusted OR (aOR) = 1.94, 95% CI = 1.06-3.56] and housing renovation (aOR = 1.94, 95% CI = 1.03-3.67) during the periconceptional period were positively related to a greater risk of all CHDs, similar results were also found in isolated CHDs rather than multiple CHDs. Additionally, living near main roads was positively associated with secundum atrial septal defect/patent foramen ovale (aOR = 2.65, 95% CI = 1.03-6.81) and housing renovation was strongly positively associated with ventricular septal defect (aOR = 5.08, 95% CI = 2.05-12.60). However, no association was observed between incense burning and family relationships and all CHDs, isolated and multiple CHDs and CHDs subtypes. Conclusion Living near main roads and housing renovation during the periconceptional period are significantly associated with the increased risks for all CHDs and isolated CHDs. Further study is needed to extend sample size to explore the effects of time and frequency of burning incense and family relationships on CHDs in offspring.